2022
DOI: 10.1111/hepr.13835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of patients with chronic liver disease in Japan related to alcohol use: Nationwide examination using alcohol use disorders identification test

Abstract: Aim: Patients often do not respond truthfully to physicians' interviews concerning alcohol. Few reports regarding the level of alcohol dependence in patients with chronic liver disease (CLD) have been presented. This study aimed to elucidate severity distribution in patients with CLD using the alcohol use disorders identification test (AUDIT). Methods: From March to June 2022, 2034 Japanese outpatients with CLD, including 415 cases associated with hepatitis C virus, 436 with hepatitis B virus, 173 with alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Alcohol intake leads to increased portal hypertension, reported to be caused mainly by compression of the hepatic sinusoids due to hepatocyte ballooning [29], while intake of a high concentration of ethanol increases endothelin-1 and induces contraction of hepatic sinusoids [30]. In another study, interviewing that included the alcohol use disorders identification test (AUDIT) showed that not a small percentage of chronic liver disease outpatients have harmful alcohol harmful use (AUDIT 8-14: HCV:HBV:alcohol-related liver disease:others = 5.8%: 8.9%:24.3%:4.4%) or alcohol dependency (AU-DIT ≥15: HCV:HBV:alcohol-related liver disease: others = 3.4%:3.0%:27.7%:1.9%) [31]. Thus, lifestyle habits, especially alcohol intake, associated with increased portal hypertension can be an uncertain clinical factor.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol intake leads to increased portal hypertension, reported to be caused mainly by compression of the hepatic sinusoids due to hepatocyte ballooning [29], while intake of a high concentration of ethanol increases endothelin-1 and induces contraction of hepatic sinusoids [30]. In another study, interviewing that included the alcohol use disorders identification test (AUDIT) showed that not a small percentage of chronic liver disease outpatients have harmful alcohol harmful use (AUDIT 8-14: HCV:HBV:alcohol-related liver disease:others = 5.8%: 8.9%:24.3%:4.4%) or alcohol dependency (AU-DIT ≥15: HCV:HBV:alcohol-related liver disease: others = 3.4%:3.0%:27.7%:1.9%) [31]. Thus, lifestyle habits, especially alcohol intake, associated with increased portal hypertension can be an uncertain clinical factor.…”
Section: Discussionmentioning
confidence: 99%